Модифікований квантовий алгоритм шора для пошуку дискретного логарифму - Максутов, Д. С. (ХНУРЕ, 2019)
The given work is devoted to the modern developments in the field of quantum computer algorithms related to cryptanalysis. The major topic of the work is a modification of the Shor quantum algorithm that is designed to solve a discrete logarithm problem. The work also contains information about the current state of quantum computing technologies and known non-quantum solutions to the discrete logarithm problem. The aim of the work is to demonstrate that nowadays-cryptographic systems based on Elliptic-curve cryptography (ECC) are vulnerable to quantum algorithms or will be vulnerable in the near future.